2016
DOI: 10.1186/s12864-016-2565-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential responsiveness of Holstein and Angus dermal fibroblasts to LPS challenge occurs without major differences in the methylome

Abstract: BackgroundWe have previously found substantial animal-to-animal and age-dependent variation in the response of Holstein fibroblast cultures challenged with LPS. To expand on this finding, fibroblast cultures were established from dairy (Holstein) and beef (Angus) cattle and challenged with LPS to examine breed-dependent differences in the innate immune response. Global gene expression was measured by RNA-Seq, while an epigenetic basis for expression differences was examined by methylated CpG island recovery as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Just as with the age difference, we have shown that dermal fibroblasts collected from the Holstein breed are much more responsive to LPS than fibroblasts collected from the Angus breed [26]. To determine whether similar gene expression differences could be detected between breeds, RT-qPCR was performed on age-matched dermal fibroblast cultures at 0, 2 and 8 h post-LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Just as with the age difference, we have shown that dermal fibroblasts collected from the Holstein breed are much more responsive to LPS than fibroblasts collected from the Angus breed [26]. To determine whether similar gene expression differences could be detected between breeds, RT-qPCR was performed on age-matched dermal fibroblast cultures at 0, 2 and 8 h post-LPS treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Although expression of SAA3 was higher in HR animals at all 3 time points, no significant differences were measured, and the weak induction of SAA3 post-LPS stimulation suggests that more time may be required following LPS treatment for IL-6 to elicit its effect on SAA3 expression. Finally, expression of CCL20, a CC-motif chemokine that is induced in response to E. coli mastitis (Petzl et al, 2012) and has been shown to differ in expression in 2 other groups of HR and LR fibroblast cohorts (Green et al, 2015;Benjamin et al, 2016), was measured. The chemokine was highly upregulated by 2 h post-LPS treatment and, overall, expression was higher in HR cells, but again the difference did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Gene Regulation in Ruminants: A Nutritional Perspective DOI: http://dx.doi.org /10.5772/intechopen.82193 In a study aiming to use the fibroblast model to explore differences between a dairy breed (Holstein) and a beef breed (Angus) in their innate responses to LPS exposure, several immune-associated differentially expressed genes between breeds were found [124]. Within them, TLR4, which is the extracellular receptor responsible for recognition of LPS presented higher level of expression in Holstein cows as compared to Angus, suggests the Holstein animals will detect and respond to Gram-negative bacteria more vigorously than Angus animals.…”
Section: Example Of Nutrigenomics Linkage Between Beef and Dairy Cattlementioning
confidence: 99%
“…While a beef calf usually stays with the dam approximately until 6-7 months old, a dairy calf is separated from its mother as soon as it finishes consuming colostrum or earlier. Although there are studies that started to analyze the epigenetic differences between breeds [124], this is a promising area that needs to be studied in deep.…”
Section: Example Of Nutrigenomics Linkage Between Beef and Dairy Cattlementioning
confidence: 99%